2009
DOI: 10.1177/1065912909343583
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Context, and Television Advertising: A Comprehensive Analysis of 2000 and 2002 House Races

Abstract: Are men and women portrayed differently in campaigns? Much scholarship and commentary expects that this is so, yet previous studies provide ambiguous evidence on the extent of gender difference.The authors provide a comprehensive analysis of gender differences in television advertisements in congressional races in 2000 and 2002 with data that allow them to take into account the frequency of airings, the sponsorship of the advertisements, partisanship, and competitiveness of the race. Although some gender diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 58 publications
2
43
0
6
Order By: Relevance
“…Research suggests male candidates rely on feminine stereotypes in campaign advertising and on their websites(Dolan, 2005;Sapiro, Walsh, Strach, & Hennings, 2011); and some feminine traits such as honesty and empathy are important leadership traits(Funk, 1999;Miller, Wattenberg, & Malanchuk, 1986).…”
mentioning
confidence: 99%
“…Research suggests male candidates rely on feminine stereotypes in campaign advertising and on their websites(Dolan, 2005;Sapiro, Walsh, Strach, & Hennings, 2011); and some feminine traits such as honesty and empathy are important leadership traits(Funk, 1999;Miller, Wattenberg, & Malanchuk, 1986).…”
mentioning
confidence: 99%
“…Dolan's (2005) examination of the websites of candidates for Congress in 2000-2002 found that female and male candidates campaigned on similar issues and what appeared to drive campaign issues was the candidate's party. Looking at House races in the same year, Sapiro et al (2011) examined television ads produced by candidates and parties/groups and reached similar conclusions.…”
Section: Literature Reviewmentioning
confidence: 70%
“…Even though there are solid reasons to expect sex differences in candidates' attention to women's issues, recent research has had a difficult time finding significant differences (Dolan, 2005;Sapiro, Cramer Walsh, Strach, & Hennings, 2011). Although research from the 1980s and 1990s tended to find significant differences between male and female candidates, such that female candidates were more likely to campaign on social policies including children issues, education, environment, and abortion (Kahn, 1993;la Cour Dabelko & Herrnson, 1997;Robertson, Froemling, Wells, & McGraw, 1999), research conducted during the 21st century has not.…”
Section: Literature Reviewmentioning
confidence: 90%
“…When Kim Kahn () conducted research on female underrepresentation in public office, she found gender differences in the messages candidates offered voters through televised campaign advertisements. A recent article by Sapiro and others () finds no gender differences in candidate, party, or interest group sponsored ads in the 2000 and 2002 election cycles. Kathleen Dolan's () research on candidate self‐presentation via the web during the 2002 election cycle also suggests little gender difference.…”
Section: Resultsmentioning
confidence: 96%